2017
DOI: 10.18388/abp.2015_1215
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of E-cadherin and increased sialylation level in clear cell renal cell carcinoma

Abstract: Cancer cells are characterized by an aberrant increase in protein N-glycosylation and by disruption of E-cadherin-mediated adherens junctions. However, the relationship between alterations in N-glycosylation process and loss of E-cadherin adhesion in cancer remains unclear. The mechanisms of altered expression of adhesive glycoproteins in cancer cells have not been fully elucidated. Thus, the aim of this study was to examine the expression of E-cadherin and sialyl Lewis/, NeuAcα2-3Gal, NeuAcα2-6Gal/GalNAc stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In clear cell RCC, upregulation of protein glycosylation in cancer cells may be useful in diagnosis and determining disease prognosis . Furthermore, N‐glycosylation is involved in cell adhesion and is associated with reduced expression of E‐cadherin, which modulates the metastatic potential of cancer cells . We hypothesize that this pathway might contribute to cancer pathogenesis such that upregulation of PMM2 might enhance cancer cell aggressiveness by increased N‐glycosylation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In clear cell RCC, upregulation of protein glycosylation in cancer cells may be useful in diagnosis and determining disease prognosis . Furthermore, N‐glycosylation is involved in cell adhesion and is associated with reduced expression of E‐cadherin, which modulates the metastatic potential of cancer cells . We hypothesize that this pathway might contribute to cancer pathogenesis such that upregulation of PMM2 might enhance cancer cell aggressiveness by increased N‐glycosylation.…”
Section: Discussionmentioning
confidence: 98%
“…Protein glycosylation is an important contributor to cancer progression, including cell growth, tumor‐induced immunomodulation, and eventual metastasis . Previous reports indicated that cancer cells, including RCC, are characterized by an aberrant increase in protein N‐glycosylation . In clear cell RCC, upregulation of protein glycosylation in cancer cells may be useful in diagnosis and determining disease prognosis .…”
Section: Discussionmentioning
confidence: 99%